Key working and the quality of relationships in secure accommodation - Amy McKellar; Andrew Kendrick (Scottish Journal of Residential Child Care)
This article discusses the findings of a study which aimed to gain an insight into the views of young people in secure accommodation and their residential workers about the quality of relationships and, in particular, to explore the role of the key worker. Five themes were identified in the research: participation in the matching process between young people and residential workers; the level of consistency in the relationship between key worker and young person; the scope of the key worker role in secure care; the frequency and purpose of key time; and the barriers to achieving key time. The findings are located in the broader literature about the importance of relationships in social work and residential child care.